Barriers to co-operation and competitive advantage: Crossborder business networks of Saxon and Northern Bohemian firms - Birgit Leick (Journal for East European Management Studies, 2011)
Small-scale business co-operation across borders is considered as major driving force of economic integration between Western and Central Eastern Europe. In this context, it is argued that business co-operation and networks support the creation of competitive advantage. This paper sheds new light on this issue by adding a case study of firms in selected East German and Czech border regions. The study focuses on two inter-related research questions: Can firms create competitive advantage in small-scale business co-operation and networks within border regions? And what role is there for the barriers to cooperation that firms encounter? These questions are investigated using a dataset of nearly 60 structured interviews with firms from the cross-border regions. – – In der Theorie kommt Unternehmenskooperationen und -netzwerken in Grenzräumen eine hohe Bedeutung bei der ökonomischen Integration der peripheren Regionen West- und Mittelosteuropas zu. Es wird angenommen, dass solche kleinräumigen Netzwerke einen wichtigen Beitrag zur Erhöhung der Wettbewerbsfähigkeit der Unternehmen in den zumeist wirtschaftlich strukturschwachen Regionen an der früheren EU-Außengrenze leisten. Der vorliegende Beitrag untersucht vor dem Hintergrund dieser Hypothese, ob Unternehmenskooperation und -netzwerke im Grenzraum tatsächlich die Wettbewerbsfähigkeit der beteiligten Unternehmen erhöhen und welche Rolle in diesem Zusammenhang Kooperationshemmnisse spielen. Als Fallbeispiel dient der Grenzraum Sachsen (Deutschland) - Nordböhmen (Tschechische Republik). Dem empirischen Teil liegt ein qualitativer Ansatz zugrunde; die Datenbasis besteht aus rund 60 Interviews mit Unternehmen in Sachsen und Nordböhmen.
Keywords: 650; Cross-border business co-operation; competitive advantage; barriers to co-operation; Central Eastern Europe; East Germany